Regionalisation and global governance : the taming of globalisation? - Cooper, Andrew Fenton, 1950-; Hughes, Christopher W.; Lombaerde, Philippe de.; University of Warwick. Centre for the Study of Globalisation and Regionalisation; Economic and Social Research Council (Great Britain) (London ; New York : Routledge, Taylor & Francis Group, 2008)
'The relationship between global governance and regionalisation is fraught with ambiguity. Understanding regionalisation in this context requires an understanding of its relationship, and reactive condition, with both the constellations of global governance and globalisation.''The expert and multi-disciplinary editors and contributors survey the context as well as the general character of these projects, together with their links as both parallel mediating mechanisms and distinctive choices for interjecting governance into globalisation. Examining these projects in tandem amplifies their importance and enables the authors to tease out coincidental as well as alternative possibilities in policy direction.''This book will be of interest to students and scholars of international relations, area studies, international economics, international political economy, political science, public administration and development studies.'--Jacket.
Introduction : regionalisation and the taming of globalisation? / Andrew F. Cooper, Christopher W. Hughes, and Philippe de Lombarde -- Enhancing global governance through regional integration / Ramesh Thakur and Luk van Langenhove -- Studying regionalisation comparatively : a conceptual framework / Alex Warleigh-Lack -- The future of regionalism : old divides, new frontiers / Bjn Hettne and Fredrik Serbaum -- Rethinking classical integration theory / Ben Rosamond -- Regional multinationals and the myth of globalisation / Alan M. Rugman -- The role of regional agreements in trade and investment regimes / Stephen Woolcock -- No safe havens : labour, regional integration, and globalisation / Robert O'Brien -- Regionalisation and responses to armed conflict, with special focus on conflict prevention and peacekeeping / Kennedy Graham -- Non-traditional security in Asia : the many faces of securitisation / Mely Caballero-Anthony -- Making cultural policy in a globalising world / Patricia M. Goff -- Regionalism in global governance : realigning goals and leadership with cultures / Martin Albrow and Colin I. Bradford -- Executive but expansive : the L20 as a project of'new' multilateralism and new regionalism / Andrew F. Cooper.
'Centre for the Study of Globalisation and Regionalisation; Economic & Social Research Council.'
Includes bibliographical references and index.
Electronic version is available via MyiLibrary.
Mode of access: Internet via World Wide Web.
Keywords: Regionalism; Globalization -- Political aspects; International organization